Analysis of the intensity of social media use, digital marketing exposure, and its effect on consumptive behavior - P Mumu, Noldy D.; Seran, Patrisius; Soeradi, Yoga (Institute of Computer Science (IOCS), 2023)
The research aims to determine the Influence of Social Media Use and Digital Marketing Exposure on the Consumptive Behavior of Urban Communities in the city of Kupang. The variables used in this study are social media, digital marketing, and consumptive behavior. Based on the results of the analysis and discussion obtained the conclusion: The use of social media has no effect on the Consumptive Behavior of the Urban Community of Kupang City, this is evidenced by T counting 1,651 < T table 2,001 and the significance level of 0.104 > 0.05. While Digital Marketing Exposure on social media has a positive and significant effect on the Consumptive Behavior of The Urban Community of Kupang City, this is evidenced by 4,986 > T table 2,001 and the significance level of 0.00 < 0.05. While the Use of social media and Digital Marketing Together affects the Consumptive Behavior of the Urban Community of Kupang City, evidenced by the coefficient of determination (R2) of 0.485 or 48.5%. Based on the R2 value of 0.485 where the influence together between the independent variables of Social Media Use (X1) and Digital Marketing Exposure (X2) on the dependent variables of Consumptive Behavior of The Urban Community of Kupang City (Y) is only 48.5%, while the remaining 51.5% is influenced by other variables outside the research, further research is needed on the other variables in question